2013
DOI: 10.1089/hum.2012.037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of DNA Vaccines Forming E7 Recombinant Retroviral Virus-Like Particles for the Treatment of Human Papillomavirus-Induced Cancers

Abstract: Human papillomavirus (HPV) is involved in the development of anogenital tumors and also in the development of oropharyngeal head and neck carcinomas, where HPV-16, expressing the E6 and E7 oncoproteins, is the most frequent serotype. Although vaccines encoding L1 and L2 capsid HPV proteins are efficient for the prevention of HPV infection, they are inadequate for treating established tumors. Hence, development of innovative vaccine therapies targeting E6/E7 is important for controlling HPV-induced cancers. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 48 publications
3
24
0
2
Order By: Relevance
“…In agreement with this hypothesis, previous studies using DNA vaccines carrying the HPV E6 or E7 genes alone or combined with different antigens from various viruses could induce specific T cell lymphocytes against papillomavirus in vitro and in mouse models (Lescaille et al, 2013;Santana et al, 2013). But in early clinical trials, no correlation between cytotoxic activity and the poor clinical outcome was detected for DNA vaccines (Garcia et al, 2004;Trimble et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…In agreement with this hypothesis, previous studies using DNA vaccines carrying the HPV E6 or E7 genes alone or combined with different antigens from various viruses could induce specific T cell lymphocytes against papillomavirus in vitro and in mouse models (Lescaille et al, 2013;Santana et al, 2013). But in early clinical trials, no correlation between cytotoxic activity and the poor clinical outcome was detected for DNA vaccines (Garcia et al, 2004;Trimble et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…Also circulating NAbs were maintained over a longer period of time and could be boosted by additional plasmo-retroVLP delivery [72]. Later studies, using animal models, showed that plasmo-VLPs were able to prime APCs and to generate protective immune response for HCV, HIV and appear as a promising strategy for the treatment of HPV-induced cancers [41,56,57,73].…”
Section: Hybrid Vaccine Designsmentioning
confidence: 99%
“…We have previously demonstrated that MVA E2 recombinant virus is capable of eliminating cervical Intraepithelial lesions grade 1, 2 and 3 in a therapeutic vaccination protocol. 27 We attempted to analyze cytotoxic T-cell activity against HPV-infected cells in all patients before and after treatment with MVA E2. This is the first report to demonstrate that MVA E2 can eliminate HPV lesions in patients with RRP.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report to demonstrate that MVA E2 can eliminate HPV lesions in patients with RRP. [26][27][28] Although the mechanism of action is not well understood, cidofovir is known to induce apoptosis and stimulate the immune system against virus-infected cells. However, these patients are being followed up to assess the ability of the MVA E2 vaccine to protect against recurrence in the longer term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation